2018
DOI: 10.1080/07481187.2018.1469054
|View full text |Cite
|
Sign up to set email alerts
|

How religious and spiritual beliefs explain prolonged grief disorder symptoms

Abstract: This study investigated the importance of religious and spiritual beliefs in daily life in explaining prolonged grief disorder (PGD) symptomatology. Participants were 588 bereaved adults who completed a questionnaire. The importance of spiritual beliefs in daily life explained a small to medium, significant 3% of variance in PGD symptoms, but religious beliefs in daily life did not. Individuals who placed moderate importance on spiritual beliefs in their daily life may experience more intense grief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…As indicated by the opinions of the patients expressed in this and other studies, patients who suffer less and feel better use strategies to cope with their illness and give meaning to their lives (Moreira et al 2017;González-Barón et al 2005). People with spiritual beliefs experience less intense pain (Christian et al 2018); specifically, the level of suffering of patients in spiritual palliative care decreases at the end of life (Rufino-Castro 2015) Various studies highlight the positive effect of the presence of clergy as a spiritual support (Balboni et al 2013;Ferrell et al 2008). Any type of spiritual support or practice can generate hope and help individuals express their feelings (Simão-Miranda et al 2017;Ando et al 2009;Herth 2000), for example using rituals and ritual-like acts (Van der Weegen et al 2019), by promoting the resilience capacity (Barreto et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As indicated by the opinions of the patients expressed in this and other studies, patients who suffer less and feel better use strategies to cope with their illness and give meaning to their lives (Moreira et al 2017;González-Barón et al 2005). People with spiritual beliefs experience less intense pain (Christian et al 2018); specifically, the level of suffering of patients in spiritual palliative care decreases at the end of life (Rufino-Castro 2015) Various studies highlight the positive effect of the presence of clergy as a spiritual support (Balboni et al 2013;Ferrell et al 2008). Any type of spiritual support or practice can generate hope and help individuals express their feelings (Simão-Miranda et al 2017;Ando et al 2009;Herth 2000), for example using rituals and ritual-like acts (Van der Weegen et al 2019), by promoting the resilience capacity (Barreto et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Grief and bereavement are natural and universal human experiences, which occur before, during, and after a significant person in someone's life dies . However, just as the circumstances surrounding every death are varied, each individual can experience bereavement in different ways, which may reflect the nature of the death, their relationships, their social supports, and cultural context . Most people find ways to deal with grief and bereavement over time, with the needs of bereaved individuals largely met through obtaining support within their existing networks such as family and friends.…”
Section: Introductionmentioning
confidence: 99%
“…One of the results of the papers also showed that well-being is developed by the spiritual domain (34). In addition spiritual influenced the quality of life (19), related to meaning of life (20) self-acceptance (26), and healthy behavior (38,27) (table 1, table 3). Based on these papers, it can be concluded that spiritual care is needed by patients, so it was needed to depict clear definition of spiritual care.…”
Section: Discussionmentioning
confidence: 99%
“…This study was a review and conducted for quantitative research. This study following the guideline for Preferred Reporting Items for Systematic Review and Meta-Analyzes (PRISMA) (19) and using previous study for guiding the review (20). This study using CINAHL database for searching spiritual care original study.…”
Section: Methodsmentioning
confidence: 99%